Sosial Media sebagai Media Kampanye Partai Politik - Yulius, Mikhael; Rusadi, Udi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
The development of information technology is currently growing rapidly. The use of social media as an effective tool for political campaigns has been widely reported in several studies. The power of social media has fueled transparency and supported e-democracy around the world. Citizens have the freedom to choose the best candidate to represent them in parliament. This study aims to examine the role of social media as a campaign media for political parties (political parties). This study was a descriptive study with secondary data. The results of the study showed that there were several factors that affect the electability of general elections. They can also be influenced by the existence of social media accounts for each candidate or political party to attract sympathizers. The use of social media by political parties was carried out by almost all political parties in Indonesia, so that political parties with a low existence rate compared to elite political parties had a greater effort to demonstrate the capabilities of these political parties. Another advantage of the use of social media by political parties was that they were able to embrace more sympathizers from the younger generation, for example Gen Z and Millennials. This was expected to significantly increase public participation in political activities for all people and generations.